New directions processing of technogenic waste of the copper industry - B. R. Vokhidov; A. S. Khasanov; B. M. Nemenenok; G. F. Mamaraimov (Литьë и металлургия)
At the present time, in the mining and metallurgical industry there are trends in the processing of man-made waste that have accumulated over the course of many years. Since the world’s reserves of ore deposits with a high initial content of non-ferrous metals and easily processed ores are currently practically depleted. This is due to a decrease in the volume of processing of conditioned ores and the involvement in the development of industrial waste, refractory ores and off-balance from low-grade dumps. High prices for metals on the world market create a favorable environment for the development of technologies for the extraction of precious metals involving the processing of mineral resources of technogenic origin. The work studies the mineralogical composition of industrial waste from the copper industry in the conditions of JSC “Almalyk MMC”, determined the effectiveness of methods for the selective extraction of platinoids and paid attention to the methods of dissolution, reduction of platinum metals and methods of their purification from various impurities. Based on the study of this topic and the analysis of the results of the research, the authors proposed an optimal technology and complex methods for extracting platinum, palladium and rhodium from industrial waste using selective methods suitable for each metal separately using hydrometallurgy and pyrometallurgy. Hydrometallurgical methods have been developed for the purification of palladium, platinum and rhodium with treatment, respectively, with formic, citric and nitric acids. As a result of the developed technologies, the possibility of complex extraction of platinum group metals from industrial waste has been achieved. In this case, the end-to-end extraction of all platinoids is over 80 %.